Effects of plyometric jump training on jump and sprint performance in young male soccer players: A systematic review and meta-analysis - Ramirez-Campillo, R.; Castillo, D.; Raya-González, J.; Moran, J.; Sáez de Villarreal, E.; Lloyd, R. S. (Sports Medicine, 2020)
Background: Even from a young age, modern soccer requires high levels of physical fitness development, particularly jumping and sprinting. Plyometric jump training (PJT), combined with young athletes` regular soccer sessions, has the potential to improve jumping and sprinting. However, studies exploring the effects of PJT are generally limited by small sample sizes. This problem of underpowered studies may, thus, be resolved by pooling study results in a meta-analysis.